Novel﻿ markers to early detect degradation on cellulose nitrate-based heritage at the submicrometer level using synchrotron UV–VIS multispectral luminescence - Neves, Artur (2022)
20200316 H2020-NMBP‐35‐2017 CORES-PD/00253/2012 PD/BD/136678/2018 UIDB/ 50006/2020 UIDP/50006/2020